ANALISIS POTENSI SUMBERDAYA PERIKANAN WILAYAH PESISIR DALAM MENUNJANG KESEJAHTERAAN NELAYAN DI DISTRIK MIMIKA BARAT KABUPATEN MIMIKA - Erwin Erwin; Leonardus Tumuka (JURNAL KRITIS (Kebijakan, Riset, dan Inovasi), 2018)
This study aim to the determine the potential of fishery resources in supporting the welfare of fishermen in the Western district of Mimika, the research method used is descriptive research method, the research method describes something such as the state of the situation, events, and others. Data collection method using observation, interview, quesioneer and documentation. To know the potential of fishery resources, the anatlytical instrument used in this research is situation analysis using SWOT analysis. The result of this study indicate that the position of fishery resources in the districk of Western Mimika, lies the opportunity (quadran) 1? which means this situation is very profitable. The situation has opportunity and power to be strengthened by taking advantage of opportunities, but on the other hand the situation of fishery resources in West Mimika District also faces some internal constraints/ weakness and external threats.